2022
DOI: 10.1002/nop2.1412
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of family‐centred auditory and tactile stimulation implementation on traumatic brain injured patients

Abstract: Aim To determine the outcomes of Family‐centred Auditory and Tactile Stimulation Implementation on Traumatic Brain Injured Patients in Egypt. Background Family engagement in the care of their relatives in the Intensive care units is limited due to patients' life‐threatening conditions, in addition to the use of high technology in these settings. Auditory and tactile sensory stimulations are among the diverse sensory stimulations that have received more attention in brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…148 Even among comatose patients, tactile or auditory stimulation may elicit a response that cannot be elicited by medical team members, suggesting that familiar voices and presence may aid in recovery. 149 Critical care survivors and their caregivers can be considered to be co-survivors. They are both at a similar risk of developing psychological impairments and a reduced quality of life.…”
Section: Family and Caregiver Picsmentioning
confidence: 99%
“…148 Even among comatose patients, tactile or auditory stimulation may elicit a response that cannot be elicited by medical team members, suggesting that familiar voices and presence may aid in recovery. 149 Critical care survivors and their caregivers can be considered to be co-survivors. They are both at a similar risk of developing psychological impairments and a reduced quality of life.…”
Section: Family and Caregiver Picsmentioning
confidence: 99%
“…Long-term caregivers fully understand patients and provide medical staff with information about patients' interests and hobbies before illness, creating a more suitable environment for patients to recover. Several reports at home and abroad have evaluated the effectiveness of family members' participation in sensory stimulation in promoting consciousness disturbance [23][24][25][26][27]. Hu et al showed that emotion could affect the encoding of data in memory to remember the stimuli better.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have proved that the presence of family members can significantly enhance a patient's physical and mental well-being, by reducing anxiety and stress [1,2]. Additionally, emotional support has been identified as crucial for arousal in comatose patients [3][4][5]. However, providing reassurance can be challenging, especially when patients cannot communicate effectively.…”
mentioning
confidence: 99%